NETFLIX CONSUMER PREFERENCE ANALYSIS - Annissa, Isti; Susilawati, Wati; Suseno, Novie; Hamdani, Nizar Alam (Universitas Pendidikan Indonesia, 2020)
The increase in the number of internet users has led to the emergence of many innovations from service providers such as website-based buying and selling services (e-commerce), e-learning, social media, and platforms that offer streaming services like music videos. Â This research aims to find out how the preferences of NetFlix consumers and some of the existing attributes. The research method used is a survey method. The approach used in this research is quantitative. The data was collected using interviews using questionnaires. Total sample of 30 using a simple random sampling technique. Analysis of preference data with the conjoined method. In the overall statistics section, it is known that the perceived price attribute has the highest level of importance